Charge- and Size-Selective Molecular Separation using Ultrathin Cellulose Membranes - Puspasari, Tiara; Yu, Haizhou; Peinemann, Klaus-Viktor (ChemSusChem, 2016)
To date, it is still a challenge to prepare high‐flux and highselectivity microporous membranes thinner than 20 nm without introducing defects. In this work, we report for the first time the application of cellulose membranes for selective separation of small molecules. A freestanding cellulose membrane as thin as 10 nm has been prepared through regeneration of trimethylsilyl cellulose (TMSC). The freestanding membrane can be transferred to any desired substrate and shows a normalized flux as high as 700 L m−2 h−1 bar−1 when supported by a porous alumina disc. According to filtration experiments, the membrane exhibits precise size‐sieving performances with an estimated pore size between 1.5–3.5 nm depending on the regeneration period and initial TMSC concentration. A perfect discrimination of anionic molecules over neutral species is demonstrated. Moreover, the membrane demonstrates high reproducibility, high scale‐up potential, and excellent stability over two months. A new fate for cellulose: A 10 nm thick freestanding cellulose membrane has been conveniently prepared through regeneration of trimethylsilyl cellulose. It shows as much as 700 L m−2 h−1 bar−1 flux when supported by an alumina disc. Within an estimated pore size between 1.5–3.5 nm, a perfect discrimination of anionic molecules over neutral species is demonstrated. The membrane demonstrates high reproducibility, high scale‐up potential, and excellent stability over a two‐month period.